A comparative study of combined treatments for enhanced early-age cracking control of self-consolidating concrete. (10th July 2020) - Cao, Qi; Wang, Ruibin; Jia, Jinqing; Zhou, Changjun; Lin, Zhibin
Highlights: Polypropylene fiber shows the best cracking control ability among the three materials. Combined use of expansive agent and lightweight aggregate improves the cracking control ability. Combined use of expansive agent and fiber improves the cracking control ability. When fiber content is 0.1%, the lightweight aggregate has no obvious crack control. Abstract: Concrete bridge deck and other concrete civil structures often experience severe early-age cracks, mainly due to thermal and shrinkage stresses during concrete curation and hydration. Nowadays, several treatments for crack control of concrete (e.g., the incorporation of PP fiber, internal curing materials, or expansive agent) have been proposed and proved effective, but there are very limited studies on the combined effect of PP fiber, internal curing material and expansive agent. Therefore, this study tended to provide a comprehensively comparative investigation of individual treatment and their combined effects on effectiveness of crack control. A total of 18 mixture proportions of self-consolidating concrete (SCC) with different ratios (or dosages) of three treatments were designed and were quantified for their early age cracking control. The results showed that the combined treatments provided different perspectives for effectively cracking control for SCC samples, as compared to individual ones. The results demonstrated that either PP fiber with EA or LWA with EA offered considerably improved cracking control, as compared to those of individual treatments. Particularly, when at low PP fiber content (i.e., 0.05% vol.), the cracking control of SCC was significantly improved to a certain extent with increase of LWA ratio. However, at higher PP fiber content of 0.1% vol., LWA did not show significant effect on improving concrete cracking control.